Cluster randomized control trial to test the impact of participatory extension delivery versus traditional extension delivery on adoption of agroecological practices and home garden farming methods: Training manual - Gupta, Shweta; Alvi, Muzna; Singh, Sonali (CGIAR System Organization, 2025)
This study aims to understand the impact of participatory extension approach on adoption of agroecological farming practices versus traditional extension approach among smallholder farmers. We assess how information delivered through different approaches impacts farmers' agroecological knowledge, the adoption rate of agroecological practices along with homestead-based farming models based on agroecological principles, and analyze its effects on agricultural, household, and individual outcomes.